2023
DOI: 10.1038/s41598-023-30221-x
|View full text |Cite
|
Sign up to set email alerts
|

Targeted delivery of paclitaxel drug using polymer-coated magnetic nanoparticles for fibrosarcoma therapy: in vitro and in vivo studies

Abstract: Fibrosarcoma is a rare type of cancer that affects cells known as fibroblasts that are malignant, locally recurring, and spreading tumor in fibrous tissue. In this work, an iron plate immersed in an aqueous solution of double added deionized water, supplemented with potassium permanganate solution (KMnO4) was carried out by the pulsed laser ablation in liquid method (PLAIL). Superparamagnetic iron oxide nanoparticles (SPIONs) were synthesized using different laser wavelengths (1064, 532, and 266 nm) at a fluen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 94 publications
(59 reference statements)
0
13
0
Order By: Relevance
“…The functionalization of iron oxide nanoparticles with targeting ligands, antibodies, or peptides might enhance their selectivity towards cancer cell receptors or markers, facilitating targeted delivery of drug molecules (as doxorubicin and paclitaxel) [23,76] and short ribonucleotides (e.g., miRNAs, siRNAs) [132,133].…”
Section: Carbon Nanomaterialsmentioning
confidence: 99%
See 1 more Smart Citation
“…The functionalization of iron oxide nanoparticles with targeting ligands, antibodies, or peptides might enhance their selectivity towards cancer cell receptors or markers, facilitating targeted delivery of drug molecules (as doxorubicin and paclitaxel) [23,76] and short ribonucleotides (e.g., miRNAs, siRNAs) [132,133].…”
Section: Carbon Nanomaterialsmentioning
confidence: 99%
“…Magnetic nanoparticles have been adroitly harnessed in the domain of hyperthermia therapy, leveraging the application of alternating magnetic fields to selectively induce controlled hyperthermic effects within cancer cells. Clinical trials have been conducted to assess the feasibility and therapeutic potential of this methodology, particularly for distinct malignancies [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Commercial MNPs frequently possess an intrinsic negative charge [ 125 ]. To explain this phenomenon, Al-Obaidy and colleagues [ 126 ] evaluated the physiochemical characteristics of SPIONs in vitro and in vivo. They found that the negative zeta-potential charge of SPIONs effectively prevented the formation of aggregates, resulting in suitable polydispersity ratios.…”
Section: Implications and Future Directionsmentioning
confidence: 99%
“…For instance, hydrophilic polymeric nanoparticles enhance drug solubility in aqueous environments, elevating bioavailability, facilitating intracellular drug delivery, and extending drug half‐lives. [ 15–17 ]…”
Section: Introductionmentioning
confidence: 99%
“…For instance, hydrophilic polymeric nanoparticles enhance drug solubility in aqueous environments, elevating bioavailability, facilitating intracellular drug delivery, and extending drug half-lives. [15][16][17] The dimensions of DDSs play a pivotal role in dictating their cellular uptake, with nanosystems within the range of 100-200 nm exhibiting optimal uptake rates. [18][19][20][21] Within this specific size interval, there is a propensity for macrophages, vital constituents of the immune system, to engulf larger nanoparticles.…”
Section: Introductionmentioning
confidence: 99%